Comparison of the efficacy and safety of sublingual misoprostol (PGE1) versus intracervical dinoprostone (PGE2) for induction of labour: a prospective study - Agarwal, Neha; Raghav, Priyanka; Singh, Saroj; Pathak, Anu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Induction of labour is indicated when the benefits of induction to either mother or fetus outweigh those of pregnancy continuation. Various mechanical methods include use of extra amniotic saline infusion, artificial rupture of membranes, balloon tipped catheter, natural and synthetic laminaria or stretch sweep method. Pharmacological methods are mainly using prostaglandins either Dinoprostone (PGE2) or Misoprostol (PGE1). This study aimed to compare the efficacy and safety of sublingual Misoprostol (PGE1) versus intracervical Dinoprostone (PGE2) for induction of labour and to compare maternal and perinatal outcome in both groups. Methods: In this study, 250 antenatal women with 35 weeks or more period of gestation with a single live fetus, cephalic presentation were included for induction of labour.125 women received 25mcg misoprostol sublingually (group A) and 125 women received 0.5mg of dinoprostone intracervically (group B). Results: There was shorter induction to active phase interval (7.68±3.39 vs 11.42±5.43 hours), induction to delivery intervals (11.46±3.46 vs 16.23±5.61 hours) and less requirement of oxytocin augmentation (25.6% vs 73.6%) in misoprostol group than dinoprostone group. Mode of delivery, maternal and neonatal complications were similar in both groups. Conclusions: Use of sublingual misoprostol in lower dose is a safe and cost-effective method for induction of labour.